Enhancing Student Comprehension of Audio Mixing and Mastering Through Jigsaw Activity : A Study of Pedagogical Impact - Ezra Alfandy, M Duin; Doris, Maying; Madzlan, Abet (International Journal of Communication Networks and Information Security (IJCNIS), 2024)
Audio mixing and mastering are always being teach as a practicebased learning. The student-centered learning for this topic is related when student use their understanding and develop their skills in listening while adjusting knobs or audios technical which contributed to their final project. Jigsaw activity approaches is being selected to determine the student’s understanding towards audio mixing and mastering in practice-based learning. A quantitative and content analysis method is being conducted for this study. The method of jigsaw activity had been practiced in the class session which the result varied in four activities that being prepared to analyze the student’s understanding. The four activities are preparing slides, quiz, practical hands on, and questionnaire. The results shown the jigsaw contributed on enhancing student’s understanding towards mixing and mastering activities. Although the students applied their understanding more on the practical activities, the jigsaw activity still influence towards the student’s understanding in practice-based learning subject.